Financial Literacy, Income and Self-Control on Financial Management Behavior of Generation Z - Citra Anjani; Darto Darto (BASKARA : Journal of Business and Entrepreneurship, 2023)
In the current era of globalization, economic circulation continues to change and gradually spread throughout the world, including Indonesia. One of the factors influencing these changes is financial behavior. Therefore, financial knowledge is absolutely important the community, because financial knowledge covers how individuals manage their finances properly. Often, individuals fail to manage their finances not because of their low income but because of their ignorance in managing and allocating their finances properly. The purpose of this study was to find out whether there is influence from financial literacy, income, and self-control variables on the financial management behavior of Generation Z, especially students at universities like Muhammadiyah Jakarta. The method used in this study is a quantitative approach with primary data obtained from distributing questionnaires. The data analysis technique used by the researcher uses the classical assumption test, multiple linear regression, T test, and hypothesis test. The questionnaire distribution period was carried out in October–November 2022. The results of this study indicate that the variables financial literacy, income, and self-control have a positive and significant effect on the financial management behavior of generation Z.